.7(.3x-.8)=-4.48

Simple and best practice solution for .7(.3x-.8)=-4.48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .7(.3x-.8)=-4.48 equation:


Simplifying
0.7(0.3x + -0.8) = -4.48

Reorder the terms:
0.7(-0.8 + 0.3x) = -4.48
(-0.8 * 0.7 + 0.3x * 0.7) = -4.48
(-0.56 + 0.21x) = -4.48

Solving
-0.56 + 0.21x = -4.48

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.56' to each side of the equation.
-0.56 + 0.56 + 0.21x = -4.48 + 0.56

Combine like terms: -0.56 + 0.56 = 0.00
0.00 + 0.21x = -4.48 + 0.56
0.21x = -4.48 + 0.56

Combine like terms: -4.48 + 0.56 = -3.92
0.21x = -3.92

Divide each side by '0.21'.
x = -18.66666667

Simplifying
x = -18.66666667

See similar equations:

| d^3+1=0 | | 2x^2+50x-20x=0 | | 3x+5(15)= | | 1369373+6472= | | 2y-4x=18 | | 66=3(2x-4) | | 10-8(x-6)=2-4x | | 3(16)-4y= | | 32=(g*7)-(g*3) | | GivenA= | | 20(10-x)-200(9-x)=2000 | | 25z^2=1 | | 5/6r-1/3r | | -5x-6x=-5+3 | | 45+4*12=61+4*12 | | 4y-6=3y+25 | | 3m^2+72=33m | | -6(-7x-1)=-8x+9(-3x-4) | | 13-8x+1139=0 | | x^2+49=6 | | 2(1+7x)-3(x-3)=+55 | | 2x+5=-75+8x | | 2x+5=20-x | | -18-9m=m^2 | | 6x+22=14x-17 | | 1/3-40.90 | | 5x+30=10x+40 | | 40.90-1/3 | | 13x^2+11x-24=0 | | -7(8k-4)-7(k-6)=7 | | -7(8k-4)-7(k-6)= | | 3x+1/2-x=6x-4/7 |

Equations solver categories